Total recall : my unbelievably true life story - Schwarzenegger, Arnold (New Delhi Simon & Schuster, 2013)
Total Recall is the unbelievably true story of Arnold Schwarzeneggers life. Born in the small city of Thal, Austria, in 1947, he moved to Los Angeles at the age of 21. Within ten years, he was a millionaire business man. After twenty years, he was the worlds biggest movie star. In 2003, he was Governor of California and a household name around the world.
Keywords: Bodybuilders; Motion picture actors and actresses; Politicians; Autobiography